A COMPARATIVE ANALYSIS OF DDR4 AND DDR5 MEMORY ARCHITECTURE - Endita Layla Sulistiyowati; Aprillia Rahmasari Distiah; Nisa Ulin Ni'mah; Allifa Maulani; Aisyah Dwi Windarti; Noviara Zizi Amanda (Journal of Data Analytics, Information, and Computer Science, 2026)
The development of modern software demands high data transfer rates from the main memory. However, increasing conventional RAM speed is often hindered by thermal law limitations, triggering circuit temperature spikes due to forced clock speeds. This study aims to analyze DDR5 memory data bus path structural modifications in overcoming these semiconductor circuit physical limitations. The method employed is a literature study with a qualitative-descriptive approach, utilizing secondary data from Google Scholar, Garuda, and technical specification documents. The study scope is strictly confined to internal micro-architectural modifications, excluding memory capacity and density scaling parameters. Results indicate that increased data transfer rates in the DDR5 generation are achieved by restructuring the single 64-bit data bus path into a dual 32-bit sub-channel system. This modification combines with doubling the Burst Length value to BL16 to transmit large data packets simultaneously without frequent processor interruptions. In conclusion, this internal architectural engineering provides an effective solution to accelerate data transmission and maintain temperature stability without forcing memory physical frequency limits. Theoretically, these findings shift the memory optimization paradigm from frequency scaling to structural path efficiency, foundational for future scalable hardware designs.